Superfoods: Enhancing Cognitive Function and Memory Retention Through Dietary Choices and Nutrition - Bagas (Mandalika Journal of Medical and Health Studies, 2025)
This qualitative study explores the role of superfoods in enhancing cognitive function and memory retention through a systematic review of existing literature. Using a library research approach, this paper synthesizes current scientific findings from peer-reviewed journals, clinical trials, and meta-analyses that examine the neuroprotective and cognitive-enhancing properties of various nutrient-rich foods. The study focuses on key dietary components found in superfoods such as omega-3 fatty acids, flavonoids, polyphenols, antioxidants, and B vitamins, which have been shown to positively influence brain health. Drawing upon empirical studies in the fields of neuroscience and nutritional epidemiology, this review identifies several superfoods—including blueberries, fatty fish, walnuts, green leafy vegetables, and turmeric—that demonstrate measurable effects on brain plasticity, cognitive processing speed, and memory consolidation. The results suggest that regular dietary intake of these superfoods can mitigate age-related cognitive decline, reduce oxidative stress, and support long-term neurological health. Furthermore, the study discusses the mechanisms through which these nutrients impact brain function, including improved synaptic signaling, anti-inflammatory actions, and enhanced cerebral blood flow. While acknowledging the limitations of existing research—such as small sample sizes and the need for longitudinal data—this paper highlights the potential of dietary interventions as complementary strategies to improve cognitive resilience. The findings underscore the importance of integrating superfood consumption into daily dietary habits as a non-pharmacological, accessible approach to cognitive health promotion. Future research should aim to conduct large-scale, longitudinal studies to further establish causality and refine dietary guidelines for optimal brain health.